Health-related quality of life of elderly with chronic obstructive pulmonary disease from selected government institution - Yahya, Nor Farahain; Omar, Noraida; Adznam, Siti Nur’ Asyura; Daut, Ummi Nadira; Mohd Yusof, Barakatun Nisak (Nutrition Society of Malaysia, 2019)
Introduction: It is widely recognised that health-related quality of life (HRQOL) is impaired in chronic obstructive pulmonary disease (COPD) patients. Most previous studies were conducted among the younger adult population and there is limited information on the elderly population. This study aimed to determine the COPD assessment test (CAT) score in the elderly with COPD. Methods: This was a crosssectional study involving 140 elderly patients who had been diagnosed with COPD at two selected government institutions. Data on socio-demographic and health status were collected by interviewing patients and reviewing their medical records. The HRQOL was measured using CAT. The independence sample t-test and one-way ANOVA were conducted to compare the CAT scores with socio-demographic and health status. Results: The socio-demographic and health characteristics of the patients were as follows: majority (54%) were aged 60-70 years, male (97%), Malay (59%), married (75%), ex-smokers (72%), had attained primary education (48%), had co-morbidities (54%), no history of hospitalisation or visits to the emergency department due to COPD (57%), and were in moderate stage of airflow obstruction (53%). The mean of CAT score was 21.87±6.85 and the majority of the patients were classified as having worst symptoms of COPD (93%) as they had high CAT score which was ≥ 10. Conclusion: Majority of the patients in this study had high scores of CAT, which indicated poor HRQOL. Ex-smokers had higher scores compared to non-smokers. More attention need to be given to these subgroups in order to increase their quality of life.